Evaluación de Eficiencia Radial en el Sector Agroindustrial a Través del Modelo DEA VRS con Salidas no Deseadas - Alfonso lizarazo, Edgar Hernán; Gutiérrez Franco, Edgar (Ingeniería, 2006)
The objective of this paper is to asset the technical efficiency of plot suppliers of raw material (bunch palm) necessary to process the different products of a firm producer of pal oil through the model VRS (variable return to scale) with undesirable outputs of focus DEA (Data Envelopment Analysis).This model modified is very uswful as this paper shows, especially en the oil palm industry where the raw material has a great impact in the eficiency of production.The efficient frontier is builded by the quality of bunches at the moment of gathering determinated by the number of mature bunches, overmature bunches, rotten bunches, sick bunches obtained in a sample. In the same way is taking into account the area of the land and the number of plants cultivated.